Hess, Sabine, Johannes Moser und Maria Schwertl (Hg.) (2013) Europäisch-ethnologisches Forschen. Neue Methoden und Konzepte. Berlin: Reimer, 322 S., 11 Abb., Index - Blätter, Andrea (Ethnoscripts, 2016)
Rezension